Effectiveness Of Face-To-Face, Online And Mixed Peer Review Formats On Undergraduates’ Writing In English In A Malaysian University - Moloudi, Mehrdad (2010)

(untitled)
In this study, an attempt is made to investigate Face-to-face Peer Review (FFPR), Online Peer Review (OLPR) and the combination of these formats - usually known as Mixed Peer Review (MPR) - and their effectiveness on Malaysian undergraduates' writing in English at Universiti Putra Malaysia (UPM). A total of 174 Malaysian undergraduates were selected through non-probability convenient sampling as the participants in this study. On week one of the study, the participants were required to answer two questionnaires (Computer Attitude Scale & Writing Attitude Scale) and sat for their writing proficiency pretest - TOEFL Test of Written English (TWE). Within the first two weeks, participants were trained how to review their peers' writings face-to-face or/and online. On week 13, they sat for their posttest which was another TOEFL TWE. The research was conducted within the fourteen-week semester during which the participants reviewed their peers' writing face-to-face or/and online. The quantitative results accompanied with the obtained qualitative data revealed that the three peer review formats (FFPR, OLPR and MPR) affected proficiency, content, organization, cohesion, vocabulary, grammar, punctuation, and spelling of Malaysian undergraduates' writing in English significantly. However, none of the peer review formats was found to be more effective than the other. Qualitatively, it was revealed that ESL tutors found the peer review formats useful and effective in improving Malaysian undergraduates' writing in English. Moreover, the Malaysian undergraduates found the peer review formats extremely effective and helpful in improving their writing in English. The effectiveness of both classic and digital formats of peer review in the Malaysian undergraduates' writing in English supported the need to include peer review in ESL writing instruction and underscore its value in providing feedback on students' performance. As one of the implications in this study, while planning the peer review sessions, ESL students' behavior should be taken into account and teachers should monitor the process and intervene where necessary. Moreover, the use of peer review guidelines and the appropriate training to ensure the success of the peer review is suggested. Another implication is that the combination of teacher and peer review is seen as supportive to the ESL students' self-directed feedbacks. It is also suggested that deeper analysis of the peers' comments as well as of the actual changes incorporated into the students' essays will definitely provide deeper insight of the peer review as a complicated and multi-dimensional process.